EFFECTS OF IMAGE PLANE, PATIENT POSITIONING, AND FORAMINAL ZONE ON MAGNETIC RESONANCE IMAGING MEASUREMENTS OF CANINE LUMBOSACRAL INTERVERTEBRAL FORAMINA. Issue 2 (16th November 2016) - Zindl, Claudia; Tucker, Russell L.; Jovanovik, Jelena; Gomez Alvarez, Constanza; Price, David; Fitzpatrick, Noel
Abstract : Degenerative lumbosacral stenosis has been suspected to have a dynamic component, especially regarding encroachment of the L7 nerve roots exiting the lumbosacral foramina. Angled cross‐sectional imaging of the neuroforamina has been found improve the accuracy of the diagnosis of stenosis in humans. In this anatomic study, foraminal apertures were evaluated by MRI at the entry, middle, and exit zones of the nerve roots in 30 dogs that were clinically affected by lumbosacral disease. Standard vs. oblique planar orientation and neutral vs. hyperextended positioning of the lumbosacral area were compared by measuring the median values for entry, middle, and exit zones. The neuroforaminal area acquired using oblique plane acquisition was significantly smaller than standard parasagittal measurements. Furthermore, standard parasagittal neuroforaminal dimensions in the hyperextended position were significantly smaller than standard parasagittal measurements in the neutral position. This statistical difference was even more pronounced for neuroforaminal dimension evaluated in the oblique plane and hyperextended position. Positioning of the dog during imaging has a significant effect on neuroforaminal dimension, corroborating the notion that spinal position may influence neural claudication in clinically affected patients. Reductions in neuroforaminal dimension are more evident on oblique planar image acquisition, suggesting that this approach may be more useful than parasagittal imaging as a tool for identifying subtle changes in L7 neuroforaminal dimensions in cases of canine lumbosacral stenosis.